Study of the water regime of plants in the conditions of Zhezkazgan city - Maksutbekova, G.T.; Akhmatov, M.K. (Fundamental and Experimental Biology, 2018)
Results of researches on assessment of a water regime of leaves and water-retaining ability of some woody and shrubby plants in the conditions of the city of Zhezkazgan relating to three ecological groups in relation to moistening conditions are given in article. Results have shown that the greatest water-retaining ability xerophytes plants, the smallest to mesophytes possess. Following the results of researches all species have been divided into 3 groups: with low (from 0 to 40 %), average (from 40 to 70 %) and high (over 70 %) water-retaining ability. Syringa josikaeahas entered into the first group; in the second — Populus alba, Malus sieversii; in a third — Berberis vulgaris, Elaeagnus oxycarpa, Amygdalus nana, Betula pendula, Crataegus sanguinea, Acacia alba, Pinus sylvestris, Juniperus sabina, Juniperus vulgaris. It should be noted that among mesophytes one species — Syringa josikaeahas entered into group with low indicators of the water mode, then Amygdalus nanahas entered into the second groups and Crataegus sanguinea— in the third the steadiest. Among mesoxerophytes in the 2nd group of stability are Malus sieversiiand Populus alba, the others have entered into the third group. Among xerophytes all species have appeared in the third group of stability. We recommend to enter plants from the third group into mass gardening of the Zhezkazgan region, the second group — it is limited on condition of regular watering, the first group — only for private gardening on plentiful watering.